Using media to improve the informed consent process for youth undergoing pediatric endoscopy and their parents - Yeh, Debra M.; Chun, Stanford; Terrones, Laura; Huang, Jeannie S. (Endoscopy International Open, 2017)
Background and study aims Youth undergoing pediatric endoscopic procedures and their parents demonstrate suboptimal comprehension of the informed consent (IC) process. We developed informational videos discussing key IC elements for pediatric endoscopy and evaluated their effects on youth and parental comprehension of the IC process.Patients and methods A randomized controlled trial of the video intervention was performed among youth undergoing endoscopy and their parents at an academic children’s hospital. Randomization occurred at the time of enrollment using permutated blocks. Following the IC process with the proceduralist, subjects underwent structured interviews to assess IC comprehension. An Informed Consent Overall Score (ICOS: range 0 – 4) for comprehension was calculated.Results Seventy-seven pairs of children and their parents participated. Intervention recipients (N = 37 pairs) demonstrated higher ICOS scores as compared to control counterparts (mean (standard deviation): 3.6 (0.7) v. 2.9 (0.9), intervention v. control parents, P < 0.0001 and 2.7 (1.1) v. 1.7 (1.1), intervention v. control youth, P < 0.0001). Conclusions A media intervention addressing key elements of the IC process for pediatric endoscopy was effective in improving comprehension of IC for youth undergoing endoscopic procedures and their parents.